Design and modelling of permanent magnet machine's windings for fault-tolerant applications - Arumugam, Puvaneswaran (2013)
The research described in this thesis focuses on the mitigation of inter-turn short-circuit (SC) faults in Fault tolerant Permanent Magnet (FT-PM) machines. An analytical model is proposed to evaluate the inter-turn SC fault current accounting for the location in the slot of the short-circuited turn(s). As a mitigation strategy to SC faults at the design stage, a winding arrangement called VSW (Vertically placed Strip Winding) is proposed and analysed. The proposed analytical model is benchmarked against finite element (FE) calculation and validated experimentally. The results demonstrate that the proposed winding arrangement in the slot improves the fault tolerance (FT) capability of the machine by limiting the inter-turn SC fault current regardless the fault location in the slot.